Design of an antibacterial gelatin based on a covalent protein–protein coupling. Issue 15 (24th December 2014) - Lequeux, Isabelle; Ducasse, Emmanuel; Jouenne, Thierry; Thebault, Pascal
ABSTRACT An antibacterial peptide (AMP), i.e., nisin, was covalently bound to gelatin through a protein–protein coupling. Various reaction conditions were tested to study and optimize parameters of grafting e.g., orientation and density of AMP, which could impact the final antibacterial activity of the modified biopolymer. Modification was investigated by Fourier transform infrared (FT‐IR) spectroscopy and zeta potential. The antibacterial activity of the nisin‐enriched gelatin was evaluated against two staphylococci bacterial strains, i.e., Staphylococus epidermidis and Staphylococcus aureus. A higher activity was found for gelatin modified at pH = 7.4 revealing an influence of the nisin orientation on the protein antibacterial property. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41825.